Pericardial Cyst in a Neonate - Dicky A Hanafy; Puti Sarah Saus; Poppy S Roebiono; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2007)
Pericardial cyst is a rare entity, often discovered incidentally on routine chest radiographs. Some studies reported an incidence of about 1:100.000. Symptomatic cysts presenting in the neonatal period are very rare. Most of the patients are asymptomatic, but can cause symptoms when they undergo complications or on account of their large size. We describe the case of a neonate presenting with tachypneau where a pericardial cyst was diagnosed with echocardiography and computer tomography, the cyst was successfully resected with open heart surgery.